Debate sobre la indeterminación de la traducción lingüística propuesta por W.V. Quine (2012)
With this article I wanted to invite to a discussion in front of the proposal of Quine who poses the hypothesis of the indeterminacy of the linguistic translation. I would like to move the debate that rid around this hypothesis, to the field of the natural sciences in order to find the foundation of a new system of rationality that can overcome the positivist model of science, which with its reductionist assumptions, hinders the interdisciplinary work proposed in times of globalization. In the Quine's proposal, in my view, we can find valuable theoretical elements that open up possibilities for new paradigms of the science.